PHYSICOCHEMICAL CHARACTERISTICS OF BOTTOM SEDIMENT OF THREE SEASONAL PONDS OF RAWATBHATA, CHITTORGARH DISTRICT (RAJASTHAN) - SARANG, N; SHARMA, L L (Journal of the Inland Fisheries Society of India, 2021)
Physico-chemical characteristics of the three seasonal ponds of Rawatbhata, Rajasthan were studied during November 2004 to November 2005. Various parameters of bottom sediment such as pH, Ec, available phosphate, available nitrogen, organic carbon, free calcium carbonate and soil texture were found to be grossly near interrelated. The pH of three seasonal ponds always remained neutral. On the basis of soil texture, the sediments of Jharjhani and Tamlao ponds could be placed under ‘loamy sand’ whereas Deeppura pond sediment has been designated as ‘loam’. Study of various Physico-chemical factors indicated that these seasonal ponds are suitable for pisciculture and particularly for rearing of fish seed. However, proper awareness about culture technology should be made available to the villagers for full utilization of available aquatic resources.Key words: Bottom sediment, physico-chemical factors, seasonal pond